The English Education Students’ Perceptions of Using Authentic Materials to Enhance Critical Thinking in the EFL Classroom: Pre-service teachers Insights into How Real-World Texts Support Higher-Order Thinking Skills - Christianti Tri Hapsari; Amelia Putri Ardianti (JADEs Journal of Academia in English Education, 2025)
This study explores English teachers’ perspectives on the use of authentic texts in language learning. It aims to provide a clear understanding of how teachers perceive and apply authentic texts in various classroom contexts. The research focuses on identifying teachers’ attitudes, strategies, and challenges in integrating authentic materials into teaching practices. The urgency of this research is located on the increasing demand for 21st-century education that develops students' abilities to think critically, solve problems, and apply knowledge in real-life contexts. A qualitative descriptive approach is employed, using an open-ended questionnaire as the main instrument to capture teachers’ experiences and perspectives. The collected data will be analyzed thematically to reveal patterns and key issues emerging from teachers’ responses. The findings are expected to contribute both theoretically and practically by offering insights into effective and contextual English language teaching. Furthermore, the study benefits pre-service teachers, especially seventh-semester students of English Education programs, by helping them connect theoretical knowledge with real classroom practices. Ultimately, this study seeks to bridge the gap between pedagogical theory and teaching reality in EFL classrooms.